2015
DOI: 10.1097/ncc.0000000000000216
|View full text |Cite
|
Sign up to set email alerts
|

Family Caregivers of Patients With a High-Grade Glioma

Abstract: Professional caregivers should be aware of the subtle balance between family caregivers' wish to care and the burden of caregiving. Professional caregivers can be of great value to family caregivers by providing guidance and assistance for this new caregiving role while being considerate of their commitment and their grief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 16 publications
0
34
0
Order By: Relevance
“…Second, and similar to previous studies [58,59] the SWB score was higher than the normative values at all test points showing that patients experience increased social support from friends and families, which might lead to an improvement of the HRQOL. Third, previous study confirms that hope is a source of strength that helps individuals to remain active [60,61], brings purpose and meaning to life, encourages a positive attitude and improves psychological well-being [62]. EWB was related to the level of functional status [63], and the 1-year survivors had higher KPS values compared to the primary sample throughout the study, which could be the reason for the increase in the EWB.…”
Section: Discussionmentioning
confidence: 59%
“…Second, and similar to previous studies [58,59] the SWB score was higher than the normative values at all test points showing that patients experience increased social support from friends and families, which might lead to an improvement of the HRQOL. Third, previous study confirms that hope is a source of strength that helps individuals to remain active [60,61], brings purpose and meaning to life, encourages a positive attitude and improves psychological well-being [62]. EWB was related to the level of functional status [63], and the 1-year survivors had higher KPS values compared to the primary sample throughout the study, which could be the reason for the increase in the EWB.…”
Section: Discussionmentioning
confidence: 59%
“…While most factors within our model have been identified in previous research on family caregiving experiences which include motives, 7,13,25 problems and challenges, 13,14,2635 actions and strategies, 13,30,36,37 consequences, 13,18,31,32,38,39,54 and social support in caregiving, 13,40,41 we found some new factors in strategies and consequences: sharing care, making sacrifices, and family cohesiveness. Our study also confirms that financial circumstances can be described both as a condition and as a consequence.…”
Section: Discussionmentioning
confidence: 79%
“…It has previously been shown that relatives are a vulnerable group in terms of mental health, with the relatives’ anxiety being at its highest before chemoradiotherapy and remaining high over time [ 27 ]. Worse scores among relatives can be related to a deeper insight into the disease and its prognosis, the personality changes that patients undergo [ 28 , 29 ], as well as the consequence of these combined factors on family life [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other possible explanations for worse scores in the group of relatives might be uncertainty about the surgery, the fear of being forced to take care of the patient, or being left alone. These feelings can at the other hand also be mixed with feelings of gratitude and privilege of taking care of the patient [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%